Unitatea de fabricație produse medicinale veterinare Delos Impex și evoluția pe piața internațională - Dan Schawlowski (Medicamentul Veterinar, 2023)
Over the past 26 years, Delos Medica has evolved, adapted and grown, but the company's mission has remained the same - improving animal health. Today, Delos Medica is an international pharmaceutical and animal health brand in the food chain, with a portfolio of over 40 manufactured and registered products, providing its medicines to some of the largest poultry farms in Europe, Asia and Middle east. Out of the desire to offer its customers the best solutions, Delos Medica began to further develop its own portfolio of veterinary medical products. The first products were drug premixes and water-soluble powders. The future plans of the company are related to the harmonious development and continuous investments in research, on the development of new products to meet the needs of the market and to become a reliable partner.